Mesoscale modeling of impact compaction of primitive solar system solids - Davison, T.; Collins, G.; Bland, Phil (Institute of Physics Publishing, 2016)
We have developed a method for simulating the mesoscale compaction of early solar system solids in low-velocity impact events using the iSALE shock physics code. Chondrules are represented by non-porous disks, placed within a porous matrix. By simulating impacts into bimodal mixtures over a wide range of parameter space (including the chondrule-to-matrix ratio, the matrix porosity and composition, and the impact velocity), we have shown how each of these parameters influences the shock processing of heterogeneous materials. The temperature after shock processing shows a strong dichotomy: matrix temperatures are elevated much higher than the chondrules, which remain largely cold. Chondrules can protect some matrix from shock compaction, with shadow regions in the lee side of chondrules exhibiting higher porosity that elsewhere in the matrix. Using the results from this mesoscale modeling, we show how the ? - a porous-compaction model parameters depend on initial bulk porosity. We also show that the timescale for the temperature dichotomy to equilibrate is highly dependent on the porosity of the matrix after the shock, and will be on the order of seconds for matrix porosities of less than 0.1, and on the order of tens to hundreds of seconds for matrix porosities of ~0.3-0.5. Finally, we have shown that the composition of the post-shock material is able to match the bulk porosity and chondrule-to-matrix ratios of meteorite groups such as carbonaceous chondrites and unequilibrated ordinary chondrites.